(untitled) (Biological Sciences - PJSIR, 2003)
The effects of soaking (Tap water, sodium bicarbonate solution) and cooking in tap water were investigated on available and unavailable carbohydrate contents and starch digestibility of black grams and chick-peas. Available carbohydrates including total soluble sugars, reducing sugars, non-reducing sugars and starch contents of these two legumes decreased to various extents as a result of soaking and cooking. From 3.43 - 25.63% total soluble sugars and 4.26 - 22.70% starch contents were lost on soaking black grams and chick-peas in tap water and sodium bicarbonate solution. Maximum amounts of total soluble sugars (28.43 - 59.64%) and starch contents (29.93 - 67.40%) were lost on cooking the water and alkali soaked legumes. However, these losses were comparatively less in case of water soaking process. Soaking and cooking processes also brought about some changes in the profile of unavailable carbohydrates of black grams and chick-peas. Soaking in sodium bicarbonate solution led to an appreciable increase of hemicellulose (42.50 - 54.31%) and NDF (28.69 - 30.68%) but not in legumes soaked in tap water. However, cooking process caused reduction in NDF (19.25 - 41.04%), ADF (5.48 - 25.31%), cellulose (12.88 - 28.42%) and hemicellulose (31.86 - 59.37%). Lignin contents of these legumes increased to some extents on cooking whereas it remained unchanged as a result of soaking . Starch digestibility of black grams and chick peas was markedly improved after cooking. However, no appreciable improvement in starch digestibility was observed after soaking these legumes in tap water or alkaline solution.